Influence of Milling Time and Ball-to-Powder Ratio on Mechanical Behavior of FeMn30Cu5 Biodegradable Alloys Prepared by Mechanical Alloying and Hot-Forging - Subbarayan Sivasankaran; Hany R. Ammar; Bandar Almangour; Samir Ali Elborolosy; Abdel-baset H. Mekky; Abdulaziz S. Alaboodi (Crystals, 2022)
FeMn30Cu5 is a biodegradable and multi-component alloy that can be used to repair bone defects in load-bearing parts in the medical field. This work focuses on studying the influence of milling time and ball-to-powder ratio (BPR) on the mechanical behavior of FeMn30Cu5 alloys via mechanical alloying and hot-forging. Three different milling times (1, 5.5, and 10 h) and BPRs (5:1, 10:1, and 15:1) were used as the main independent variables. MA was performed at 300 rpm in ethanol; the synthesized powders were dried, hot-compacted at 550 MPa, and sintered under an inert atmosphere (1000 °C, 15 min) using a medium-frequency induction furnace and hot-forging. The mechanical behavior in terms of Vickers hardness, compressive stress–strain curves, and percentage theoretical density was investigated. This experimental work revealed that both milling time and BPR significantly influenced the grain size reduction owing to variations in the severe plastic deformation and mechanical collisions produced by the milling medium. The hardness and ultimate strength of the FeMn30Cu5 alloy processed at 10 h and 15:1 BPR were 1788.17 ± 4.9 MPa, which was 1.5 times higher than those of the same alloy processed at 1 h and 5:1 BPR (1200.45 ± 6.5 MPa). Austenite iron (g-Fe), ferrite-iron (a-Fe), a-Mn, and a-Cu phases were observed in XRD and SEM images. The formed a-Mn and a-Cu overlapped with the g-Fe lattice because of the diffusion of Mn and Cu atoms during sintering and hot-forging. The incorporated 30 wt.% of Mn and 5 wt.% of Cu stabilize the austenite phase (good for MRI scans in medical applications), which contributed to promoting superior mechanical properties with milling time (10 h) and BPR (15:1) due to severe structural defects.